Mengatasi Ancaman Cyber Terhadap Privasi Data Pribadi - Anisa Puspita; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2024)
Cyber threats to data privacy are a serious challenge for every individual in this digital era. Personal data protection and digital surveillance are important in dealing with this threat. In Indonesia, cyber security challenges involve a lack of public literacy, a lack of specific government policies, and a lack of competent human resources in the field of cyber security. The method used in this research is to collect articles that have been published in national publications and use a qualitative research approach. This paper discusses cyber threats.